Investigating the effective permeability evolution as a function of hydrate saturation in the hydrate-bearing sands using a kinetic-theory-based pore network model. (October 2022) - Zhang, Yongchao; Li, Chengfeng; Ma, Jingsheng; Liu, Lele; Golsanami, Naser; Wan, Yizhao; Liu, Changling
Abstract: Permeability governs the fluid flow of hydrate-bearing sediment and affects the efficiency of natural gas production from hydrate reservoirs. The permeability in hydrate-bearings sediments is estimated empirically and appears to vary widely for sediments. This study focused on the sandy hydrate-bearing sediments and intended to elucidate the evolution of effective permeability by the mean of pore network modeling. A hydrate kinetics theory-based pore network model (KT-PNM) has been developed, in which the simulation of hydrate formation in porous media is implemented by employing two sub-processes, i.e., hydrate nucleation and hydrate growth. This KT-PNM has been applied to simulate hydrate formation in different pore networks. The permeability reduction exponent ( N ) for sandy hydrate-bearing sediments is determined to fall in the range of 3–4 based on the simulations of seven sandy samples. An empirical equation used for predicting the effective permeability in sandy hydrate-bearing sediments has been further proposed. The developed model and simulations are hoped to provide valuable insights of pore-space effects on hydrate into permeability prediction for studying the fluid seepage in hydrate-bearing sediments and facilitate the numerical simulation of gas production from the hydrate reservoirs.